Typology of Bena Traditional Architecture, Flores - Achmad, Zulkifli H (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2019)
Traditional architecture Bena has its own peculiarities and characteristics both in architectural form and in philosophy were conceived shape of the building and have a close relationship with the social and cultural setting. Characteristics of a building can sort by typology. Elements of traditional architecture can be a characteristic of the region. Making an area and remind the person or people in a given environment. Traditional building custom homes Bena community is one manifestation of which is concrete. The research method is qualitative descriptive. The purpose of this study was to determine the typology of traditional settlements Bena an attempt inventory and documentation of traditional architecture Bena. From the result of this writing, there are two forms of the observation that in macro and micro. Macro is the place to stay for people Bena while micro elements supporting the settlements and other facilities. Results of this paper show that there are two types of observations in traditional architecture itself, namely: In the macro, Sa, Pu Saka o, u, Sa, o Saka Lobo, Sa, while the micro-o Kaka is Ture Ago-Ngadha, Peo, Ngadhu, Bagha, Ture, Kapela and Gua maria.Â DOI: https://doi.org/10.26905/lw.v11i2.2980